Singing and social inclusion - Welch, Graham F.; Himonides, Evangelos; Saunders, Jo; Papageorgi, Ioulia; Sarazin, Marc (Frontiers in Psychology, 2014)
There is a growing body of neurological, cognitive and social psychological research to suggest the possibility of positive transfer effects from structured musical engagement. In particular, there is evidence to suggest that engagement in musical activities may impact on social inclusion (sense of self and of being socially integrated). Tackling social exclusion and promoting social inclusion are common concerns internationally, such as in the UK and the EC, and there are many diverse Government ministries and agencies globally that see the arts in general and music in particular as a key means by which social needs can be addressed. As part of a wider evaluation of a national, Government-sponsored music education initiative for Primary-aged children in England (‘Sing Up’), opportunity was taken by the authors, at the request of the funders, to assess any possible relationship between (a) children’s developing singing behaviour and development and (b) their social inclusion (sense of self and of being socially integrated). Subsequently, it was possible to match data from n=6087 participants, drawn from the final three years of data collection (2008-2011), in terms of each child’s individually assessed singing ability (based on their singing behaviour of two well-known songs to create a 'normalised singing score') and their written responses to a specially-designed questionnaire that included a set of statements related to children’s sense of being socially included to which the children indicated their level of agreement on a seven-point Likert scale. Data analyses suggested that the higher the normalized singing development rating, the more positive the child’s self-concept and sense of being socially included, irrespective of singer age, sex and ethnicity.